Strategi Pengenalan Candi Muaro Jambi melalui Ornamen Arca Candi pada Kain Tradisional - Aprillayalia Aghnia Rizqillah; Djoko Murdowo Murdowo (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Muaro Jambi Temples is the largest cultural heritage site in Southeast Asia, holding immense historical and cultural potential. However, the low number of visitors and limited engagement from the younger generation indicate the need for innovative approaches to promote the site. This research aims to develop a strategy for applying the ornamental sculptures of Muaro Jambi Temples to traditional textiles as a medium to introduce  and  promote Jambi’s cultural heritage. The ornaments selected include sculptures of Prajnaparamita, Dwarapala, Makara, and motifs from the main temples such as Candi Tinggi, Candi Gumpung, and Candi Gedong. The research method employed is research and development (R&D) using a design thinking approach, which involves the stages of empathize, define, ideate, prototype, and test to create motifs that preserve cultural authenticity while being suitable for textile application.  The process includes interviews with artisans, observation of traditional textile production, analysis of key challenges, brainstorming of simplified ornamental designs, prototype development, and phase evaluation with artisan and the local community. The resulting fabric prototype featuring ornamental motifs was tested during a cultural event at Muaro Jambi Temple and received positive feedback from visitors as an effective medium for introducing the history and cultural heritage of Jambi. This  study demonstrates that the application of sculptural ornaments to traditional textiles not only enhances the aesthetic value of the product but also reinforces cultural identity and increases public interest in Jambi heritage. Government support and stronger collaboration with local artisan communities are crucial to ensure that these ornament inspired textiles become a widely recognized and sustainable cultural symbol.